Achieving sustainable production and consumption of virgin plastic polymers - Grabiel, Tim; Gammage, Tom; Perry, Clare; Dixon, Christina (Frontiers in Marine Science, 2022)
The United Nations Environment Assembly (UNEA) recently adopted a resolution with a mandate to negotiate a new international legally binding instrument (a treaty) on plastic pollution. Unsustainable production and consumption of virgin plastic polymers represents the single greatest threat to preventing plastic pollution and risks undermining the incoming treaty. The justification for and benefits of a stepwise approach for controlling virgin plastic production and consumption internationally, inspired by the Montreal Protocol on Substances that Deplete the Ozone Layer, is presented.